2014
DOI: 10.1103/physrevx.4.041011
|View full text |Cite
|
Sign up to set email alerts
|

Synchronized Molecular-Dynamics Simulation via Macroscopic Heat and Momentum Transfer: An Application to Polymer Lubrication

Abstract: A synchronized molecular-dynamics simulation via macroscopic heat and momentum transfer is proposed to model the nonisothermal flow behaviors of complex fluids. In this method, the moleculardynamics simulations are assigned to small fluid elements to calculate the local stresses and temperatures and are synchronized at certain time intervals to satisfy the macroscopic heat-and momentum-transport equations. This method is applied to the lubrication of a polymeric liquid composed of short chains of ten beads bet… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(35 citation statements)
references
References 41 publications
1
33
1
Order By: Relevance
“…In Ref. [25], it is also demonstrated that an interesting re-entrant transition of the linear stress-optical relation occurs for large shear stresses because of the coupling of the conformations of the polymer chains with viscous heat generation under shear flows. Figure 2 shows the apparent viscosity of the system (a), the spatial averages of the shear stress and temperature (b) and the bond orientation tensor of the polymer chains (c) as a function of the gross shear rate.…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations
“…In Ref. [25], it is also demonstrated that an interesting re-entrant transition of the linear stress-optical relation occurs for large shear stresses because of the coupling of the conformations of the polymer chains with viscous heat generation under shear flows. Figure 2 shows the apparent viscosity of the system (a), the spatial averages of the shear stress and temperature (b) and the bond orientation tensor of the polymer chains (c) as a function of the gross shear rate.…”
Section: Resultsmentioning
confidence: 97%
“…The details of SMD method can be referred in Ref. [25]. In the following, we present quantities averaged for a long time in the steady state, in which the shear stress is spatially uniform and the time derivative of the local internal energy, i.e.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Incidentally, the multiscale hybrid method of MD and CFD is currently a very active research field [12][13][14][15][16][17][18][19][20][21][22]. The thermohydrodynamic lubrication of polymeric fluids was also investigated by the synchronized MD method, in which a transitional behavior of the polymer conformation due to thermohydrodynamic coupling was clarified [23][24][25]. Although the multiscale approach is powerful and promising for complex fluids, to further develop the multiscale method, we require more first-principles results obtained through MD simulations.…”
Section: Introductionmentioning
confidence: 99%